2022 31st IEEE International Conference on Robot and Human Interactive Communication (RO-MAN) 2022
DOI: 10.1109/ro-man53752.2022.9900772
|View full text |Cite
|
Sign up to set email alerts
|

We are all Individuals: The Role of Robot Personality and Human Traits in Trustworthy Interaction

Abstract: As robots take on roles in our society, it is important that their appearance, behaviour and personality are appropriate for the job they are given and are perceived favourably by the people with whom they interact. Here, we provide an extensive quantitative and qualitative study exploring robot personality but, importantly, with respect to individual human traits. Firstly, we show that we can accurately portray personality in a social robot, in terms of extroversionintroversion using vocal cues and linguistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 47 publications
2
6
0
Order By: Relevance
“…We also report here the strong negative correlation between Propensity to Trust (RecruitPTT) and users' negative attitude to robots after completing the experiment (ExitNARS) (Table II row 9). This confirms users with low Propensity to Trust are also likely to have a high negative attitude to robots, as seen in prior work [38].…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…We also report here the strong negative correlation between Propensity to Trust (RecruitPTT) and users' negative attitude to robots after completing the experiment (ExitNARS) (Table II row 9). This confirms users with low Propensity to Trust are also likely to have a high negative attitude to robots, as seen in prior work [38].…”
Section: Resultssupporting
confidence: 84%
“…In terms of findings, trust has been shown to play a key role in influencing acceptance of the robot. It is also interesting to see that users' satisfaction with the robot depends on individual differences, confirming previous findings [38], [43]. Thus, personalisation should be an important part of interaction design for these types of long term studies.…”
Section: Discussionsupporting
confidence: 83%
“…As mentioned above, Lim et al [8] showed that one can successfully represent extroversion and introversion using linguistic features and vocal cues, they then went on to show that an extrovert robot is preferred and trusted more than an introvert robot in a robot barista setting. We followed a similar approach to Lim et al [8], using prosodic parameters: volume, pitch, and tempo. We created two robot personalities with different traits of extroversion and introversion.…”
Section: Methodsmentioning
confidence: 99%
“…It is yet unclear if robot personality can have any effects on human proxemics behaviours, given that it has been shown that we can model certain personality traits [8]. In this study, we test if proxemics vary depending on the robot personality type.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation